A quantitative trait variant in Gabra2 underlies increased methamphetamine stimulant sensitivity. (22nd October 2021) - Goldberg, Lisa R.; Yao, Emily J.; Kelliher, Julia C.; Reed, Eric R.; Wu Cox, Jiayi; Parks, Cory; Kirkpatrick, Stacey L.; Beierle, Jacob A.; Chen, Melanie M.; Johnson, William E.; Homanics, Gregg E.; Williams, Robert W.; et al.
Abstract: Psychostimulant (methamphetamine, cocaine) use disorders have a genetic component that remains mostly unknown. We conducted genome‐wide quantitative trait locus (QTL) analysis of methamphetamine stimulant sensitivity. To facilitate gene identification, we employed a Reduced Complexity Cross between closely related C57BL/6 mouse substrains and examined maximum speed and distance traveled over 30 min following methamphetamine (2 mg/kg, i.p.). For maximum methamphetamine‐induced speed following the second and third administration, we identified a single genome‐wide significant QTL on chromosome 11 that peaked near the Cyfip2 locus (LOD = 3.5, 4.2; peak = 21 cM [36 Mb]). For methamphetamine‐induced distance traveled following the first and second administration, we identified a genome‐wide significant QTL on chromosome 5 that peaked near a functional intronic indel in Gabra2 coding for the alpha‐2 subunit of the GABA‐A receptor (LOD = 3.6–5.2; peak = 34–35 cM [66–67 Mb]). Striatal cis ‐expression QTL mapping corroborated Gabra2 as a functional candidate gene underlying methamphetamine‐induced distance traveled. CRISPR/Cas9‐mediated correction of the mutant intronic deletion on the C57BL/6J background to the wild‐type C57BL/6NJ allele was sufficient to reduce methamphetamine‐induced locomotor activity toward the wild‐type C57BL/6NJ‐like level, thus validating the quantitative trait variant (QTV). These studies show the power and efficiency of Reduced Complexity Crosses in identifying causal variants underlying complex traits. Functionally restoring Gabra2 expression decreased methamphetamine stimulant sensitivity and supports preclinical and human genetic studies implicating the GABA‐A receptor in psychostimulant addiction‐relevant traits. Importantly, our findings have major implications for studying psychostimulants in the C57BL/6J strain—the gold standard strain in biomedical research. Abstract : Identification of a quantitative trait variant in Gabra2 that underlies variation in methamphetamine stimulant sensitivity as measured via distance traveled.